Determinants of Export Performance of Malaysian Manufacturing Firms - Fellahi, Anis (2010)
Export has been identified as a key means of improving economic viability. The empirical research on the determinants of export performance has produced fragmented and conflicting results. The present study is designed to re-examine the relationship between export performance and some factors that have been frequently examined in existing export marketing literature. Specifically, this investigation contemplates the impact of firm characteristics, export marketing strategy, management perceptions, and export commitment on three non-financial measures of export performance i.e. export sales, market share, and profitability. Data was collected via a postal survey using questionnaires completed by senior managers of manufacturing firms in Malaysia. Subsequently, a descriptive analysis was used in order to delineate the salient variables affecting export performance. The findings show that, except for managers' perception of export problems, all independent variables are positively related to export performance. However, only adaptation, rather than standardization of export marketing strategies, management perception of competitive advantages, and push factors of export stimuli have significant direct impacts on export performance.